Social Networking Addiction and Social Skills in Secondary School Students - Agreda, Dessiré I. (2025)
There is discussion about the possibility of predicting and controlling addictions by intervening in social skills; the results found before are contradictory. In this study, addiction to social networks and social skill were related in predictive terms. A non-probabilistic sample of 142 high school students residing in Tacna-Peru, aged 14 to 17, was used. They were given the social network addiction questionnaire and the Goldstein social skills questionnaire. A small negative correlation was found between the dimensions of both instruments; the regression analysis allowed to identify that obsession with social networks weakly predicted changes in communication skills, alternatives to violence and pro-friendliness; and that the pro-frieidliness dimension exerts influence on obsession with social networks and lack of control; the comparative analysis found that those who use social networks more frequently are more likely to develop an addiction. On the other hand, in both the social media addiction questionnaire and the social skills questionnaire, men and women do not have differences, even when comparing the data by level of education. It is concluded that, at higher levels of addiction to social networks, there are lower social skills; and that the greater the amount of time spent using social networks, the greater the probability of addiction; the predictive analysis carried out shows weak effects. The data found can be used for the design of preventive programs.